PENGARUH METODE BERMAIN ULAR TANGGA DAN CERAMAH DALAM MENINGKATKAN PENGETAHUAN DAN SIKAP SISWA MIN TENTANG BAHAYA MEROKOK DI MIN 12 MEDAN (Fakultas Kedokteran Universitas Gadjah Mada, 2020)
ABSTRAKSmoking is still a problem in developing countries, including Indonesia. Various attempts have been made to reduce the number of smokers in Indonesia, but in reality the number of smokers increase. The behavior of smoking groups is carried out by various groups including teenagers and children. The purpose of this study was to analyze the effect of the method of playing snakes and ladders, and lecture methode in improving the knowledge and attitude of primary school students about smoking hazards in “MIN 12 “primary school.This research uses quasi experiment design. Respondents who received intervention in the study were 60 people divided into 30 people playing snakes and 30 people getting lectures. The analysis of this study used wilcoxons and Mann Whitney testHealth promotion using snakes and ladders games and lectures has been proven to increase knowledge and attitudes about the dangers of smoking. The use of the snakes and ladders game has proved to be more effective than lectures in increasing knowledge and attitudes about the dangers of smokingSnakes and ladders media should be used more often by primary schools in increasing the knowledge and attitudes of primary school students about the dangers of smoking. Elementary school principals must be more active in socializing the dangers of smoking to primary school students to prevent smoking behavior among elementary school students.